Assessment of Labor Practices in Healthcare Using an Innovatory Framework for Sustainability - Flaviu Moldovan; Liviu Moldovan; Tiberiu Bataga (Medicina, 2023)
Background and Objectives: The concept of sustainability in healthcare is poorly researched. There is a perceived need for new theoretical and empirical studies, as well as for new instruments to assess the implementation of new labor practices in the field. Such practices address unmet social needs and consolidate the sustainable development systems which promote health equity. The objective of the research is to design an innovative reference framework for sustainable development and health equity of healthcare facilities, and to provide a practical validation of this framework. Materials and Methods: The research methods consist of designing the elements of the new frame of reference, designing an indicator matrix, elaborating indicator content, and assessing the reference framework. For the assessment stage, we used sustainable medical practices reported in the scientific literature as well as a pilot reference framework that was implemented in healthcare practice. Results: The new reference framework suggested by the present study is composed of 57 indicators organized in five areas: environmental responsibility, economic performance, social responsibility, institutional capacity, and provision of sustainable healthcare services. These indicators were adapted and integrated into the seven basic topics of the social responsibility standard. The study presents the content of the indicators in the field of labor practices, as well as their evaluation grids. The innovative format of the evaluation grids aims to describe achievement degrees, both qualitatively and quantitatively. The theoretical model was validated in practice through its implementation at the Emergency Hospital in Targu Mures. Conclusions: The conclusions of the study reflect the usefulness of the new reference framework, which is compatible with the requirements in the healthcare field, but differs from other existing frameworks, considering its objective regarding the promotion of sustainable development. This objective facilitates the continuous quantification of the sustainability level, the promotion of sustainable development strategies, and sustainability-oriented approaches on the part of interested parties.